2013
DOI: 10.4140/tcp.n.2013.502
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Pharmacy Students' Attitudes Toward Nursing Facility Patients After a Geriatric Rotation

Abstract: Pharmacy students had positive attitudes toward elderly patients and nursing facilities and adequate knowledge of geriatrics after completing the geriatric rotation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
3
1
Order By: Relevance
“…Similarly, previous studies have shown that demographic factors were not related to students' attitudes toward the elderly. 20 However, in relation to gender, our study found there was a significant difference in the attitudes of male students compared to female students in mean GAS scores and the "knowledge" and the "don't know" rates on the FAQ before and after using the VIPAGE software. As gender does not appear to be a consistent predictor for better study competence, this may be associated with the .002 Taking a medical history from elderly patients is frequently an ordeal.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Similarly, previous studies have shown that demographic factors were not related to students' attitudes toward the elderly. 20 However, in relation to gender, our study found there was a significant difference in the attitudes of male students compared to female students in mean GAS scores and the "knowledge" and the "don't know" rates on the FAQ before and after using the VIPAGE software. As gender does not appear to be a consistent predictor for better study competence, this may be associated with the .002 Taking a medical history from elderly patients is frequently an ordeal.…”
Section: Discussioncontrasting
confidence: 50%
“…Similarly, a study by Sahin and colleagues determined that having an elderly relative is not a predictor of positive attitudes toward the elderly. 20 However, the significant difference in the mean GAS score of students who had elderly relatives before and after using the VIPAGE software can be explained by the fact that empathy for the elderly may be influenced by family and home experiences. This was corroborated by the study result indicating a significant change in the attitudes of those who had frequent contact with the elderly, further validating previous studies which determined that the attitudes of those who live with the elderly are more positive toward elderly people in general.…”
Section: Discussionmentioning
confidence: 99%
“…This trend of positive attitudes may be affected by the foundation that may be laid for pharmacy students who complete a focused educational activity on geriatrics. A variety of educational activities have been studied, including entire courses, workshops, simulations, gaming, health screening clinics, film studies, virtual assessments, structured interaction with seniors, and geriatrics-based rotations (e.g., long-term care facilities) [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. These studies generally involve a pre/post assessment without a control group, although there was one comparison of students who had already completed a course versus those who had not yet completed the course [ 31 ] and one service learning intervention that had a control group [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…One Canadian study from 1991 evaluated pharmacists [ 26 ], and there is one study from Saudi Arabia [ 27 ] and one from Malaysia [ 28 ]. There have been multiple studies of pharmacy students showing that educational interventions result in positive student attitudes [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. A longitudinal study found that pharmacy students maintained positive attitudes toward older adults throughout the pharmacy curriculum [ 39 ].…”
Section: Introductionmentioning
confidence: 99%